Raw and Refined Analysis on Infrastructure Productivity: An Investigation into Indian States - Unnikrishnan, Nishija; M., Biju John; Kattookaran, Thomas Paul (Indian Journal of Finance, 2024)
Purpose : The present study attempted to compare the performance of 25 major states in India concerning their infrastructure output. To provide an accurate picture, the infrastructure investment and output of each state were compared using sophisticated analysis to determine the true productivity of the Indian states. Methodology : Principal component analysis was used for raw analysis of panel data from 25 Indian states, while ordinary least square regression was used for refined analysis. The fields of electricity, building, transportation, and communication were examined in this study conducted in India. Findings : In raw analysis, states like Maharashtra, Tamil Nadu, Gujarat, Uttar Pradesh, and Karnataka performed well, and states like Goa and north-eastern states like Mizoram, Tripura, Manipur, Nagaland were poor performers. However, after a refined analysis, the actual laggards identified were Jammu and Kashmir, Jharkhand, Uttarakhand, Himachal Pradesh, Haryana, etc. While these states found it difficult to get off the ground despite receiving significant infrastructure funding, the performance of places such as Goa and other northeastern states significantly improved following the more thorough investigation. Practical Implications : The development of India is concerned with the gap in infrastructure between its states. It was advised that policymakers identify the states whose productivity is below par and come up with strategies to elevate them in order to address this. Originality/Value : The productivity of Indian states in the infrastructure sector has only been empirically studied in a few studies. It was a fresh notion to analyze infrastructure productivity using both raw and refined information, with infrastructure investment serving as a yardstick, in contrast to previous studies.